Review: Aktivitas Antioksidan Daun Kelor (Moringa Oleifera) - Fatisa, Yuni; Apruri, Azzahra Bellucci; Octarya, Zona; Fitri, Anggun Delia (LPPM Universitas Muhammadiyah Riau, 2025)
Free radicals are generated in the human body from normal metabolic processes. Apart from that, environmental factors such as UV, infrared and visible light, environmental pollution, including ozone and particulate matter and oxidative stress. The antioxidant system in the body is responsible for neutralizing or reducing the impact of free radicals in the body. If these free radicals exceed the body's antioxidant capacity, it will result in oxidative stress. There are many natural alternatives to ward off free radicals, one of which is Moringa leaves. Moringa leaves (Moringa oleifera) are found in many tropical regions, one of which is Indonesia, where they have high antioxidant activity. The method used is a literature study which is reviewed one by one, after which the journals obtained are collected and the information is compiled by summarizing the contents of the journals used as sources. This article focuses on reviewing antioxidant phytochemical compounds and the level of antioxidant activity contained in Moringa leaves. The antioxidant compounds that are abundant in Moringa leaves are a group of flavonoid compounds, namely quercetin and kaempferol. The results showed that the highest antioxidant activity.